Prognostic Value of Resection Margin Involvement After Pancreaticoduodenectomy for Ductal Adenocarcinoma: Updates From a French Prospective Multicenter Study. Issue 5 (November 2017) - Delpero, Jean Robert; Jeune, Florence; Bachellier, Philippe; Regenet, Nicolas; Le Treut, Yves Patrice; Paye, Francois; Carrere, Nicolas; Sauvanet, Alain; Adham, Mustapha; Autret, Aurelie; Poizat, Flora; Turrini, Olivier; et al.
Abstract : Objective: The aim of the study was to assess the relevance of resection margin status for survival after resection of pancreatic-head ductal adenocarcinoma. Summary Background Data: The definition and prognostic value of incomplete microscopic resection (R1) remain controversial. Methods: Prognostic factors were analyzed in 147 patients included in a prospective multicenter study on the impact of tumor clearance evaluated using a standardized pathology protocol. Results: Thirty patients received neoadjuvant treatment (NAT = 20%); 41 had venous resection (VR = 28%), and 70% received adjuvant chemotherapy. In-hospital mortality was 3% (5/147). Follow-up was 83 months. Tumor clearance was 0, <1.0, <1.5, and <2.0 mm in 35 (25%), 92 (65%), 95 (67%), and 109 (77%) patients, respectively. R0-resection rates decreased from 75% to 35% when changing the definition of R1 status from R1-direct invasion (0 mm) to R1 <1.0 mm. On univariate analysis, clearance <1.0 or <1.5 mm, pT stage, pN stage, LNR ≥0.2, tumor grade 3, and lymphovascular invasion were significantly associated with 5-year survival. On multivariate analysis, pN was the most powerful independent predictor ( P = 0.004). Clearance <1.0 or <1.5 mm had borderline significance for the entire cohort, but was relevant in certain subgroups (upfront pancreatectomy (n = 117; P = 0.049); without VR or NAT (n = 87; P = 0.003); N+ without VR or NAT (n = 50; P = 0.004). No N0-patient had R1-0 mm. Additional independent risk predictors were (1) R1 <1.0 mm for the SMA-margin in specific subgroups (upfront pancreatectomy, N0 patients without NAT, N+ patients without NAT or VR; (2) R1-0 mm posterior-margin for the NAT group ( P = 0.004). Conclusion: Tumor clearance <1.0 or <1.5 mm was an independent determinants of postresection survival in certain subgroups. To avoid misinterpretation, future trials should specify the clearance margin in millimeter. Trial registration: ClinicalTrials.gov: NCT00918853. Abstract : Supplemental Digital Content is available in the text